CONSUMER ATTITUDE AND SATISFACTION BY ONLINE APPLICATION FOR READY-TO-EAT FOOD DELIVERY SERVICE IN JABODETABEK - Kusumarini, R.R. Ajeng Pratiwi Indah; Fariyanti, Anna; Tinaprilla, Netti (Jurnal Ilmu Keluarga dan Konsumen, 2022)
The COVID-19 pandemic has made public consumption dynamic, supported by increasingly sophisticated technologies such as GoFood and GrabFood. The purpose of this study is to analyze the purchasing decision process, attitudes, consumer satisfaction and test whether there are significant differences in attitudes and satisfaction between GoFood and GrabFood customers. The design of this study was a cross section with one data collection, and the analysis used was qualitative and quantitative. The number of samples used in this study were 100 respondents from the Slovin method, then each region was divided based on the Sampling Quota. Descriptive analysis tool is used for the consumer purchasing decision process. Fishbein Multiattribute Analysis is used to analyze consumer attitudes and consumer satisfaction in this study using the Consumer Satisfaction Index (CSI) analysis. The use of nonparametric Mann-Whitney for the difference test. The results of the study show that there are five purchasing decision processes, the value of attitudes towards consumers of the GrabFood and GoFood applications with 193.88 and 193.86 points, respectively. The attitudes and satisfaction of GoFood and GrabFood consumers were not significantly different, and consumers were considered satisfied with the GoFood and GrabFood CSI scores of 79.24% and 78.16%, respectively.